Contemporary Democracy and Its Medieval Foundations: Marsilius of Padua and the Rational Justification of the Normative Principles of the State [la Democracia Contemporánea y Sus Fundamentos Medievales. Marsilio de Padua y la Justificación Racional de Los Principios Normativos del Estado] - Chapsal-Escudero, M; Castillo-Vallejos, R (Universidade Estadual Paulista (UNESP), 2018)
Through the works of Marsilius of Padua we trace sources and references that, in the context of thirteenth and fourteenth century discussions, may be seen on the margins of the foundations of contemporary democracy. The article discusses arguments related to political liberalism (Habermas), the imperative of pluralism (Rorty), and a broadening of the characterization of the social and political thinking of the Middle Ages. © 2018, Universidade Estadual Paulista (UNESP). All rights reserved.